التنشئة الاجتماعية وأثرها على أساليب المعاملة الوالدية (Comprehensive Journal of Science, 2025)
This study addressed a topic of particular scientific importance to researchers and those involved in socialization, due to its connection to children and how to raise them to be good for building a healthy society. The problem revolved around the direct impact of socialization on society. In a conscious society, we find that parental treatment differs from other societies. Therefore, this study aimed to determine the impact of socialization on parenting styles, which range between violence and indulgence. The researcher used the descriptive and analytical methodology that most social human studies rely on, in order to reach a set of results at the end of the study, which she indicated in the conclusion of the research. Among these results is that socialization has an impact on the behavior of parents in dealing with their children. She reached recommendations, including that social service providers and specialists should train parents to treat their children in a healthy manner.
Keywords: Socialization - Family - Behavior - Children - Methods.